Full constellation of clinical and radiological findings in a NF2 patient with overlapping NF1 features - Mohanty, Vivek; Nayak, Manoj Kumar (Indian Journal of Case Reports, 2020)
Neurofibromatosis is a genetic disorder of the nervous system. Patients are classified on the basis of clinical features into two types – neurofibromatosis 1 (NF1) and neurofibromatosis 2 (NF2). However, in most of the patients, all the clinical features associated with these disorders are not present. Furthermore, rarely some patients may have clinical features of NF1 overlapping with NF2. Here, we highlight an interesting case of a 24-year-old male with a history of recurrent seizures with intellectual impairment, progressive hearing, vision loss, and weakness of one side of the body. On physical examination, he had dermatological signs of NF1 in the form of café-au-lait macules and axillary freckling. Further examination revealed the presence of bilateral sensorineural hearing loss and posterior subcapsular cataract. Radiological investigation showed the presence of bilateral vestibular schwannomas and other features consistent with the diagnostic criteria of NF 2. The presence of these multiple findings along and an absence of family history made this case a rare presentation and diagnostic challenge.